Spatial quality evaluation of the elderly dormitory environment of two ILPIs located in Bauru and Marília (SP). - Rossetto, Heloisa de Freitas Zanella; Magagnin, Renata Cardoso (National Journal of City Management, 2020)
The life expectancy of the world population has increased gradually. At present, various researches seek to study elements or environments, above all, in residences that have a great impact on the quality of life and well being of this population. Dysfunctions associated with the biological-functional and cognitive system, intrinsic to the aging process, can leave the elderly susceptible to accidents (falls and bumps), due to the residential environments not offering safety to this age group. Given this context, this article aims to present the result of the evaluation of private use environments of the elderly, composed by the dormitory areas of two ILPIs located in the city of Bauru and Marília (SP), whose buildings were implanted in different periods, without the adoption of specific technical parameters for housing for the elderly. The Walkthrough technique associated with photographic record was adopted to identify the spatial quality, from positive and negative aspects, of the private environments used by elderly citizens. The results show that the spatial quality of the private environments of the analyzed institutions has more aspects considered negative than positive, especially those related to accessibility. Among the problems stand out: inadequate smooth floors, little contrast between floor plans, wall and furniture, type of frames, presence of constructive pathologies, among other problems.